NMOWChIP-seq: low-input genome-wide mapping of non-histone targets. Issue 2 (7th April 2022) - Liu, Zhengzhi; Naler, Lynette B; Zhu, Yan; Deng, Chengyu; Zhang, Qiang; Zhu, Bohan; Zhou, Zirui; Sarma, Mimosa; Murray, Alexander; Xie, Hehuang; Lu, Chang
Abstract: Genome-wide profiling of interactions between genome and various functional proteins is critical for understanding regulatory processes involved in development and diseases. Conventional assays require a large number of cells and high-quality data on tissue samples are scarce. Here we optimized a low-input chromatin immunoprecipitation followed by sequencing (ChIP-seq) technology for profiling RNA polymerase II (Pol II), transcription factor (TF), and enzyme binding at the genome scale. The new approach produces high-quality binding profiles using 1, 000–50, 000 cells. We used the approach to examine the binding of Pol II and two TFs (EGR1 and MEF2C) in cerebellum and prefrontal cortex of mouse brain and found that their binding profiles are highly reflective of the functional differences between the two brain regions. Our analysis reveals the potential for linking genome-wide TF or Pol II profiles with neuroanatomical origins of brain cells.